Senegal : Poverty Reduction Strategy Paper; Second Annual Progress Report. (IMF Staff Country Reports; Country Report, 2006)
This paper presents the Annual Progress Report (APR) 2004 on Senegal's Poverty Reduction Strategy Paper (PRSP). The APR analyzes the 2004 macroeconomic framework for the purpose of comparing the forecasts under the various scenarios and the results obtained. Budgetary programming and execution are examined, to verify their compliance with the Priority Action Plan (PAP) of the PRSP for 2004. The APR reviews policies and reforms undertaken in all the sectors, and details the execution of the PRSP matrix of measures. It also studies changes in PRSP indicators and assesses the trajectory followed in meeting objectives.